Renewable natural gas production via Sabatier reaction - Çamlık, Cansu; Çamlık, Cansu; Şeker, Erol (01. Izmir Institute of Technology, 2021)
This study attempts to understand the effect of support basicity on Sabatier reaction and improve the performance of Ni based catalysts by introducing calcium which is known for its basicity. In accordance with this purpose, Ni-Al2O3-CaO catalysts were synthesized with modified sol-gel method. Effect of Ni loading, calcination temperature and calcium content were investigated. Al2O3-CaO supports were synthesized at three ratios as follows; 70-30 wt.%, 40-60 wt.%, 10-90 wt.% wherein Ni/Al2O3 catalyst was used as reference catalyst. Based on thermodynamic analysis, reaction was conducted at 400oC and 1 atm with inlet composition of CO2/H2=1/4 and total volumetric flow rate of 100 ml/min. Reference catalyst calcined at 700oC was found to be inactive at used reaction conditions due to the presence of inactive NiAl2O4 phase. Increasing Ni loading from 1 wt.% to 10 wt.% increased both CO2 conversion and methane selectivity. Over the catalysts calcined at the temperature of 900oC, maximum methane yield was obtained over 10Ni-70Al-30Ca-900 as 8%. The influence of Ni loading was more pronounced for catalysts calcined at 700oC. In 10Ni-70Al-30Ca-700 catalyst, NiO particles were smaller than 5 nm. Therefore, it is conceivable that the alumina-calcium mixed oxide support could disperse higher loadings of Ni, which could result in higher CO2 conversion. Ca modification was found to have a prominent impact on both methane selectivity and yield. With 10Ni-10Al-90Ca-700, being best performing catalyst, CO2 conversion obtained as 76% and methane yield was 60%. The promotion of catalytic performance might arise from intensifying the CO2 chemisorption supported by XRD and TGA results.

Bu çalışma, destek bazlığının Sabatier reaksiyonu üzerindeki etkisini anlamaya ve Ni katalizörlerin kalsiyum ilavesi ile performansını iyileştirmeye çalışmaktadır. Bu amaç doğrultusunda modifiye sol-jel yöntemi ile Ni-Al2O3-CaO katalizörler sentezlenmiş ve Ni-Al2O3 katalizör referans olarak kullanılmıştır. Nikel yüklemesi, kalsinasyon sıcaklığı ve kalsiyum içeriği etkisi, katalizörlerin Sabatier reaksiyonundaki performansları doğrultusunda incelenmiştir. Termodinamik analize dayalı olarak, reaksiyon koşulları CO2/H2=1/4 giriş bileşimi ile 400oC ve 1 atm olarak seçilmiştir. 700oC'de kalsine edilen referans katalizör, NiAl2O4 fazının varlığından dolayı kullanılan reaksiyon koşullarında inaktif bulunmuştur. Tüm kalsinasyon sıcaklıklarında, Ni yüklemesinin ağırlıkça %1'den %10'a yükseltilmesi hem CO2 dönüşümünü hem de metan seçiciliğini arttırdığı gözlenmiştir. Bununla birlikte, 900oC sıcaklıkta kalsine edilen katalizörlerde, maksimum metan verimi 10Ni-70Al-30Ca-900 üzerinden %8 olmuştur. Ni yüklemesinin etkisi, 700oC'de kalsine edilmiş katalizörler için daha belirgin bulunmuştur. 10Ni-70Al-30Ca-700 katalizöründe, NiO partikülleri 5 nm'den küçük olarak bulunmaktadır. Bu nedenle, alümina-kalsiyum karışık oksit desteğinin, daha yüksek CO2 dönüşümü ile sonuçlanabilecek daha yüksek Ni yüklemelerini dağıtabileceği düşünülebilir. Kalsiyum modifikasyonunun metan seçiciliği ve verimi üzerinde belirgin bir etkisi olduğu bulunmuştur. En iyi performans gösteren katalizör olan 10Ni-10Al- 90Ca-700 ile %76 CO2 dönüşümü ve %60 metan verimi elde edilmiştir. Katalitik performansın iyileştirilmesi, bazik bir destek sayesinde CO2 kimyasal emiliminin yoğunlaşmasından kaynaklanabildiği TGA ve XRD sonuçları ile desteklenmiştir.
Sabatier Reaksiyonu ile Yenilenebilir Doğal Gaz Üretimi
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2021
Includes bibliographical references (leaves: 50-54)
Text in English; Abstract: Turkish and English
Keywords: Natural gas; Sabatier reaction; Renewable energy sources; Carbon dioxide; Nickel catalysts